Teknik Pemilihan Alat Kontrasepsi bagi Pasangan Usia Subur dengan Metode Analytical Hierarchy Process - Sunandar, Hery; Siregar, Kristian (LPPM UNIKA Santo Thomas Medan, 2018)
Contraception is an action to prevent pregnancy. Where currently there are enough tools, methods and types of contraceptives for men or women, implementation can be done in two ways, namely using contraceptive aids or without contraception. The problem that occurs in BKKBN and women's empowerment is the selection of good contraceptives used which still uses a simple computerized system that is using Microsoft Excel applications in the processing process. In solving this problem, the author uses the Analytical Hierarchy Process method to describe the weights that fit the criteria that are appropriate for the selection of family planning tools that are well used in BKKBN and women's empowerment. Analytical Hierarchy Process or often called AHP is a technique for decision making in determining the best choice from several alternatives. AHP is a mathematical model procedure that is well suited for the evaluation of qualitative attributes. These attributes are mathematically quantified in a set of comparisons in pairs. The advantages of the AHP method when compared to other decision-making methods is to have a hierarchical structure as an impact of the criteria taken, to the very detailed and detailed sub criteria